The Effect of Glycerin and Squalane on Skin Moisture in Green Tea (Camellia sinensis L.) Nanostructrure Lipid Carrier Preparation - Cynthia Gracella Gamas; Rini Dwiastuti; Lutfi Chabib (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Healthy skin requires optimal moisture levels to maintain its barrier function and prevent transepidermal water loss (TEWL). This study aims to analyze the effect of adding glycerin (humectant) and squalane (emollient) in Nanostructured Lipid Carrier (NLC) nano green tea extract (Camellia sinensis L.) preparations on skin moisture, as measured by TEWL parameters. This experimental study used three formulas: F1 (without moisturizer), F2 (with squalane), and F3 (with glycerin). Twelve healthy volunteers participated as test subjects. Physicochemical characteristics of the preparation, including organoleptic properties, pH, viscosity, particle size, PDI, and zeta potential, were evaluated. Additionally, antibacterial activity, entrapment efficiency, and TEWL values (before and after application) were measured. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test, One-Way ANOVA, and Post-Hoc Tukey HSD tests. The results showed that use of a humectant (glycerin) and an emollient (squalane) in the NLC formulation exerts an influence on the reduction of Transepidermal Water Loss (TEWL) in the skin. Based on the Post Hoc Tukey HSD test, the F1 formulation without additional moisturizer provides the most significant TEWL reduction effect compared to the F2 (with squalane) and F3 (with glycerin) formulas (p < 0.05). Meanwhile, F2 (with squalane) only shows a significant advantage compared to F3 (with glycerin) after reaching the 45th minute. This indicates that the addition of squalane as an emollient is more effective in increasing hydration and repairing the skin barrier function compared to the use of glycerin in the NLC system.